Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. Employing Artificial Intelligence in Developing Professional Development Programs  for Teachers in the Sultanate of Oman in Accordance with Transformational Leadership StandardsMr. Ali Hamad Al-Buraiki, Dr. Youssef Nait Belaid2. A Proposed Framework for Implementing Kaizen in Saudi Public Education Schools  in Light of Vision 2030Ms. Maryam Hamdan Al-Enazi3. The Degree of Pracicing Leadership Skills among Kindergarten Teachers in Dawadmi Goverment from Their Point of View and Its Relationship to Some VariablesMs. Al-Jawhara Mardas Al-Mutairi,Ms. Nuha Mishaan Al-Shammari, Ms. Atheer Saad Al-Manjoumi4. The Impact of Collaborative E-Learning on the Learning Motivation of Female Doctoral Students: A Case Study of Students in the Course on Employing Technology in EducationProf. Saida Jaser Affouneh,Ms. Eman Omar Drawshi,Ms. Areej Helmi Rabi,Ms. Reem Hani Zoubi,Ms. Sajida Sobhi Miari,Ms. Salwa Fawze Salame,Ms. Sana Fwaz Drawshy,Ms. Suheir Huleihel Nassar,Ms. Sireen Mahmood Azem,Ms. Sabrin Nor Drawshi,Ms. Safa Abdel-Kareem Asadi,Ms. Najwa Zeed Dabbah,Ms. Hiba Hasan Rabah, Ms. Wafika Ebraheem Ayoub,Ms. Wesam Dalal Khalaileh5. The Reality of the Role of Yemeni Public Universities in Cultural Awareness for Their Students During the Al-Aqsa Flood Battle and Ways to Strengthen It from the Perspective of Their Academic LeadersMr. Abdul-Raqib Qasim Ali Al Sharif6. The role of professional licensing in developing the performance of general education teachers  in the Kingdom of Saudi Arabia: opportunities and challengesMs. Samia Abdulrahman Alrifai7. The effect of students dropping out of secondary schools on their cognitive outcome  and attitude towards learning from the point of view of their teachersMr. Ayoub Suleiman Salama Al-Qarinawi ,Mr. Badi Aziz Al-Qashala8. Cyberbullying and its relationship to negative thinking among Hail University female studentsMs. Ashwag Fayz Al-Rashed, Prof. Benayan Bani Al-Rashedy
Keywords: Journal of Educational and Psychological Sciences